Exploring the Ca2+-dependent synaptic dynamics in vibro-dissociated cells. (June 2017) - Lalo, Ulyana; Pankratov, Yuriy
Graphical abstract: Highlights: Non-enzymatic vibrodissociation retains functional synapses on neuronal dendrites. Vibrodissociation enables optical monitoring of exocytosis in living cells. Synapses on dissociated neurons could be stimulated with focal electric field. This technique allows to monitor recruitment of receptors into synapses. This technique allows to study a cross-talk between postsynaptic receptors. Abstract: Dynamic alteration of the synaptic strength is one of the most important processes occurring in the nervous system. Combination of electrophysiology, confocal imaging and molecular biology led to significant advances in this research field. Yet, a progress in this area, in particular in studies of changes in the quantal behavior of central synapses and impact of glial cells on individual synapses, is hampered by technical difficulties of resolving small quantal synaptic currents. In this paper we will show how the technique of non-enzymatic vibro-dissociation, which enables to isolate living neurons avoiding artifacts of cell culture and preserving functional synapse, can be used to obtain a valuable information on fine details and mechanisms of synaptic plasticity. In particular, we will describe our recent results on Ca 2+ -dependent modulation of the postsynaptic AMPA and NMDA receptors in the individual synaptic boutons.